INFLUENCE OF NON-MODERATED AND MODERATED DISCUSSION SITES ON STUDENT SUCCESS - Kashy, Deborah A.; Albertelli, Guy; Bauer, W. (Online Learning, 2003)
One of the most successful applications of networked technology in education has been the development of individualized homework assignments. Such assignments provide immediate feedback to students and discourage copying. However, networked technology also allows students to develop sophisticated schemes designed to beat the system. This paper, supported in part by Andrew W. Mellon and Alfred P. Sloan Foundations, reports the educational outcomes for introductory physics students who used two web sites, one designed by the course instructor to provide assistance to students and the other a site designed by a third party to provide students with the solutions to problems. Results indicated that students who used the third-party site more tended to perform more poorly on all measures of success in the course, and that these relationships held even after accounting for students’ academic ability. On the other hand, students who more often used the site designed by the instructor tended to perform better in the course.